2010
DOI: 10.1103/physrevlett.105.250503
|View full text |Cite
|
Sign up to set email alerts
|

Fault-Tolerant Topological One-Way Quantum Computation with Probabilistic Two-Qubit Gates

Abstract: We propose a scalable way to construct a 3D cluster state for fault-tolerant topological one-way computation (TOWC) even if the entangling two-qubit gates succeed with a small probability. It is shown that fault-tolerant TOWC can be performed with the success probability of the two-qubit gate such as 0.5 (0.1) provided that the unheralded error probability of the two-qubit gate is less than 0.040% (0.016%). Furthermore, the resource usage is considerably suppressed compared to the conventional fault-tolerant s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…These include schemes to tolerate high rates of qubit loss [28,62,63] and a concatenated code tailored to highly dephasing-biased noise [64]. Considering other physically motivated noise models may lead to new schemes that could underpin quantum computer architectures in the future.…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…These include schemes to tolerate high rates of qubit loss [28,62,63] and a concatenated code tailored to highly dephasing-biased noise [64]. Considering other physically motivated noise models may lead to new schemes that could underpin quantum computer architectures in the future.…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…We show that the proposed architecture works well even with a gate error rate ∼ 0.1%. Furthermore, the quantum channel can be extensively noisy; the tolerable error rate is as high as 30% (fidelity 0.7), which is substantially higher than the case with the local system of a single qubit [6,7]. These results are achieved by utilizing twofold error management techniques, entanglement purification [11,12] and topological quantum computation [3] as described below.…”
mentioning
confidence: 95%
“…In this context, it has been reported that if the local system consists of only a single qubit, the tolerable rate of error in the quantum channel (or remote entangling operation) have to be as small as 0.01% [6,7], although the success probability of the channel can be very small ∼ 0.1. Then, a natural question is what happens if there are additional qubits in the local system.…”
mentioning
confidence: 99%
“…In this model, the computation proceeds by performing measurements on single qubits that are part of a highly entangled cluster state. This architecture has comparatively high fault-tolerance thresholds [3][4][5][6][7] and is therefore attractive for the practical implementation of a quantum computer. Cluster states can be created with a variety of entangling gates [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%